Efektivitas Penyaluran Program Raskin di Kabupaten Tabanan - RAHAYU, I GEDE URIF BAYU; USTRIYANA, I NYOMAN GEDE; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.2, April 2016)
Abstract Distribution the Effectiveness of Raskin in Tabanan The study was aimed to determine mechanisms to distribution Raskin, problems to distribution Raskin, and effekiviness to distribution Raskin by used descrptive method and indicators of six appropriated (right on target, right on price, right on time, right on quality, and right on administration). Samples were 73 houshold that receive most benefit of Raskin in Belimbing Village representative of the Baturiti Districts and Nyitdah Village representative of the Kediri that is beneficiaries Raskin most numerous in Tabanan. The results of the field study showed that the process implementation of Raskin program has been running well within the guidelines already assigned distribution  Raskin, to the right target indicators total percentage of  70.4% so it can be  categorized effective. for right indicator the amount total percentage of 80.5% that can be categorized effective. For right indicator the price total percentage of 93.2% that can be very categorized effective. For timely indicator of the total percentage of 78.6% that can be categorized effective. For precise indicator the quality total percentage of 83.6% that can be categorized very effective. For precise indicator the administration total percentage of 86.6% so it can be said to be very effective. process distribution Raskin to the RTS-PM seen from the  indicator sixth already according to the objectives of the government.  but not close the possibility of a slight problem in terms of target, quantity, price, time, quality and administration.
Keywords: distribution mechanism, the distribution, the measurement effectiveness